Cumulation of collective tacit knowledge in higher education. - Kirsi Liikamaa; Heli Aramo-Immonen (Spain, 2022)
More and more students in higher education are working during their studies when "anytime, anywhere" learning have added value for adults leaners [4]. The information and communication technology have been perceived as the solution to improve quality, reduce costs, and increase access [7] consequently universities are providing different multiform learning possibilities like collaborative study projects in the self-determining teams where students are working and learning together. In this study we describe Master students learning process in virtual teams in the Project Business course by using four phases of SECI model of knowledge creation. SECI model is applied to assess transforming students' individual tacit knowledge into explicit knowledge and enriching it to tacit knowledge again in the individual and the group level. [9]. In the paper is presented how the graduate students' learning process occur in a teamwork exercise. During the focal course in our study students are producing in teams essays about different project management perspectives during the four phases of SECI model. The essays are publish in essay collection.
EDULEARN17 Proceedings